The Role of Bio-based Plasticizers in Mitigating Polymer Membranes Fragility and Brittleness - Idriss, Ibrahim Maina (Balai Publikasi Indonesia, 2024)
The review article focuses on the potential of bio-based plasticizers to enhance the mechanical properties of polymer membranes, addressing the critical issues of fragility and brittleness. It highlights the environmental and health risks associated with traditional plasticizers like phthalates and also advocates for the adoption of sustainable and non-toxic bio-based alternatives. In doing so, it emphasizes the significant advancements in bio-based plasticizer research, aiming to stimulate further scientific inquiry into their application in membrane synthesis. By advocating for the adoption of green polymers, the article underscores the critical necessity for the development of environmentally benign and mechanically robust membrane technologies. These advancements hold considerable promise for a wide array of applications, notably within biomedical domains and separation processes, heralding a new era of sustainability and functionality in membrane technology